Intellectual property and the brain : how neuroscience will reshape legal protection for creations of the mind / Mark Bartholomew, University at Buffalo School of Law. - Bartholomew, Mark, 1971- (Cambridge University Press, 2022)
Although legal scholars have begun to explore the implications of neuroscientific research for criminal law, the field has yet to assess the potential of such research for intellectual property law - a legal regime governing over one-third of the US economy. Intellectual Property and the Brain addresses this gap by showing how tools meant to improve our understanding of human behavior inevitably shape the balance of power between artists and copyists, businesses and consumers. This first of its kind book demonstrates how neuroscience can improve our flawed approach to regulating creative conduct and commercial communications when applied with careful attention to the reasons that our system of intellectual property law exists. With a host of real-life examples of art, design, and advertising, the book charts a path forward for legal actors seeking reforms that will unlock artistic innovation, elevate economic productivity, and promote consumer welfare.